Distribution of Transferable Antibiotic Resistance Genes in Laboratory-Reared Edible Mealworms (Tenebrio molitor L.) - Osimani, Andrea; Milanović, Vesna; Cardinali, Federica; Garofalo, Cristiana; Clementi, Francesca; Ruschioni, Sara; Riolo, Paola; Isidoro, Nunzio; Loreto, Nino; Galarini, Roberta; Moretti, Simone; Petruzzelli, Annalisa; et al. (Frontiers in Microbiology, 2018)
In the present study, the distribution of antibiotic resistance genes in laboratory-reared fresh mealworm larvae (Tenebrio molitor L.), their feeding substrates (carrots and wheatmeal), and frass were assessed. Microbial counts on selective media added with antibiotics highlighted the presence of lactic acid bacteria resistant to ampicillin and vancomycin and, more specifically, enterococci resistant to the latter antibiotic. Moreover, staphylococci resistant to gentamicin, erythromycin, tetracycline, and vancomycin were detected. Enterobacteriaceae resistant to ampicillin and gentamicin were also found, together with Pseudomonadaceae resistant to gentamicin. Some of the genes coding for resistance to macrolide-limcosamide-streptogramib B [erm(A), erm(C)], vancomycin [vanA, vanB], tetracycline [tet(O)], and β-lactams [mecA and blaZ] were absent in all of the samples. For the feeding substrates, organic wheatmeal was positive for tet(S) and tet(K), whereas no AR genes were detected in organic carrots. The genes tet(M), tet(K), and tet(S) were detected in both mealworms and frass, whereas gene aac-aph, coding for resistance to amynoglicosides was exclusively detected in frass. No residues for any of the 64 antibiotics belonging to 10 different drug classes were found in either the organic wheatmeal or carrots. Based on the overall results, the contribution of feed to the occurrence of antibiotic resistance (AR) genes and/or antibiotic-resistant microorganisms in mealworm larvae was hypothesized together with vertical transmission via insect egg smearing.